Catalytic copyrolysis of particle board and polypropylene over Al-MCM-48. (October 2016) - Kim, Hannah; Choi, Suek Ju; Kim, Ji Man; Jeon, Jong-Ki; Park, Sung Hoon; Jung, Sang-Chul; Kim, Sang Chai; Park, Young-Kwon
Graphical abstract: Highlights: Al-MCM-48 was used for catalytic copyrolysis of particle board and polypropylene. Catalytic produced mainly hydrocarbons. The hydrocarbons produced were mainly in the diesel range. Abstract: Particle board and polypropylene (PP) at a mixing ratio of 1:1 were copyrolyzed over two Al-MCM-48 catalysts with Si/Al ratios of 20 and 80. The catalyst characteristics were examined by measuring the Brunauer-Emmett-Teller surface area, temperature programmed desorption of ammonia, and X-ray diffraction. The main pyrolysis products of particle board were oxygenates, acids, and phenolics, whereas a large quantity of hydrocarbons within the diesel fuel range was produced from copyrolysis with polypropylene. The catalytic copyrolysis of particle board and PP over the Al-MCM-48 catalysts produced bio-oil with a much larger hydrocarbon content than that from the catalytic pyrolysis of particle board only. The hydrocarbons produced were mainly in the diesel range, highlighting the potential for the production of high-quality fuel.